1994
DOI: 10.1007/bf00593508
|View full text |Cite
|
Sign up to set email alerts
|

Significance of haemorrhagic lacunes on MRI in patients with hypertensive cerebrovascular disease and intracerebral haemorrhage

Abstract: Our purpose was to determine the frequency and significance of haemorrhagic lacunes (HL) on MRI in patients with a history of, or at risk for intracerebral haemorrhage. We examined 72 patients with old spontaneous intracerebral haemorrhage (ICH) using T1- and T2-weighted spin-echo sequences. MRI studies of 137 consecutive patients with cerebrovascular disease but no known ICH were also reviewed. Both groups showed about the same degree of age-related white matter change and nonhaemorrhagic lacunar infarcts, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 31 publications
1
32
1
2
Order By: Relevance
“…4,12,13 Third, studies showed that patients with ICH had a higher frequency of microhemorrhages than those without ICH. 3,4 Therefore, the topographical similarity between hPMH and PPH may provide another clue that primary microhemorrhages could predispose to ICH and that hPMH may be a risk factor for future symptomatic and potentially catastrophic PPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12,13 Third, studies showed that patients with ICH had a higher frequency of microhemorrhages than those without ICH. 3,4 Therefore, the topographical similarity between hPMH and PPH may provide another clue that primary microhemorrhages could predispose to ICH and that hPMH may be a risk factor for future symptomatic and potentially catastrophic PPH.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Some studies suggested that microhemorrhage associated with hypertension could precede catastrophic intracranial hemorrhage (ICH). [2][3][4] However, few studies have compared the anatomic distributions of large ICHs and microhemorrhages.…”
mentioning
confidence: 99%
“…Earlier investigations that have reported a smaller rate of MBs in association with ICH have used conventional MRI sequences in all or most of their patients. 2,12 Therefore, these lower numbers most likely resulted from the inferior sensitivity of conventional T2-weighted scans in the detection of small hemosiderin deposits. A much higher detection rate of MBs has recently been documented with the use of a gradient-echo technique compared with conventional T2 sequences in a direct comparison.…”
Section: Discussionmentioning
confidence: 99%
“…6 Cerebral microhemorrhages, best visualized by MRI, result from rupture of small blood vessels in basal ganglia or subcortical white matter and are most often clinically asymptomatic. 2 Microhemorrhages were first described after the clinical use of GE MRI 2,3,7 and are usually defined as rounded foci of Ͻ5 mm in size that appear hypointense and distinct from vascular flow voids, leptomeningeal hemasiderosis, or nonhemorrhagic subcortical mineralization 2,8 (Figure). The reduction of the GE magnetic resonance (MR) signal is caused by hemosiderin, a blood breakdown product that causes magnetic susceptibility-induced relaxation leading to T2* signal loss.…”
Section: Definitionmentioning
confidence: 99%